Self-directed Groupwork – social justice through social action and empowerment. (13th March 2017) - Fleming, Jennie; Ward, Dave
Abstract : Self-directed Groupwork and its values and methodology have taken root in a range of disciplines and in peer, volunteer and professionally facilitated groups addressing a diverse range of issues and across many countries. It has promoted and sustained the mindset and practices needed for achieving social justice through social action and community empowerment. Addressing, in particular, the theories that have informed Self-directed Groupwork, we show that Self-directed Groupwork is alive and well, but argue that it is vital to re-engage with the core vision and mission and to re-energise open and honest collaboration with community members and users of services as partners in change.